2014
DOI: 10.1002/2327-6924.12106
|View full text |Cite
|
Sign up to set email alerts
|

HFE -associated hereditary hemochromatosis: Overview of genetics and clinical implications for nurse practitioners in primary care settings

Abstract: Purpose HFE‐hemochromatosis is one of the most common genetic disorders in the United States among Caucasians of Northern European ancestry. The purpose of this article is to discuss HFE‐associated hereditary hemochromatosis (HH), including the genetics, pathophysiology, phenotype and genotype, diagnostics, and management utilizing a case‐based format as an exemplar. Data sources Online genetic resources; professional guidelines; review; and scientific articles. Conclusion HFE‐HH is an autosomal recessive diso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…The functional consequences of such a decrease in RBC deformability include heightened risk for microvascular disease and organ damage, given that nutrient delivery to distal tissues may be impaired [ 23 , 24 ]. Previous studies have demonstrated that HFE-HH is closely associated with venous disease [ 25 ], and iron deposition in various tissues is closely associated with organ damage and failure [ 26 ]. Thus, altered RBC deformability may be implicit in some of the co-morbidities that accompany HFE-HH.…”
Section: Discussionmentioning
confidence: 99%
“…The functional consequences of such a decrease in RBC deformability include heightened risk for microvascular disease and organ damage, given that nutrient delivery to distal tissues may be impaired [ 23 , 24 ]. Previous studies have demonstrated that HFE-HH is closely associated with venous disease [ 25 ], and iron deposition in various tissues is closely associated with organ damage and failure [ 26 ]. Thus, altered RBC deformability may be implicit in some of the co-morbidities that accompany HFE-HH.…”
Section: Discussionmentioning
confidence: 99%
“…Inappropriately elevated serum hepcidin may reduce duodenal iron absorption, which further increases colonic adenocarcinoma iron exposure in CRC patients (Pusatcioglu et al, 2014 ). Hereditary hemochromatosis, a genetic disorder of iron overload, generally harbors inappropriately elevated intestinal iron absorption (Emanuele et al, 2014 ). In HFE-associated hereditary hemochromatosis, mutations in the HFE gene disrupt the synthesis of hepcidin (Osborne et al, 2010 ).…”
Section: Iron Is Implicated In a Variety Of Cancer Typesmentioning
confidence: 99%
“…For this reason, the set of KI’s can be used by different health care professionals, i.e. physicians (hepatogastroenterologists, hematologists, rheumatologists, general practitioners, …) as well as advanced nurse practitioners [ 22 ].…”
Section: Discussionmentioning
confidence: 99%